Antidepressant-Like Activity of Cannabinoid Type-1 Receptor Antagonist, Rimonabant: Behavioural Investigation in Animal Model of Depression - R. MAHESH,; PINKY SHARMA,; BALDEV K. GAUTAM,; SHVETANK BHATT,; DILIP. K. PANDEY, (International Journal of Pharma and Bio Sciences, 2010)
Recent ï¬ndings support the hypothesis that CB receptor blockade might be associated with antidepressant and anti-stress effects. In the current study, the anti-depressant-like effects of rimonabant were studied in validated models of depression. Rimonabant (4-8mg/kg, i.p.) significantly decreased the duration of immobility in a dose dependent manner in mice forced swim test (FST) and in tail suspension test (TST) without affecting the baseline locomotion. Rimonabant potentiated the 5-HTP induced head twitches. Rimonabant (4-8mg/kg) rimonabant significantly reversed the reserpine induced hypothermia. Interactions studies revealed that, rimonabant potentiated the antidepressant activity of standard drugs in FST and TST respectively. Further, the behaviour anomalies exhibited by olfactory bulbectomized rats (OBX) were attenuated by chronic rimonabant treatment as observed in open field test (OFT). In conclusion, this behavioral study depicts the anti-depressant-like effect of rimonabant in acute and chronic model of depression which can be useful as a powerful anti-depressant agent.